Un tema metodológico: la irrelevancia del análisis ex ante y ex post para la teoría del empleo de Keynes - Gnos, Claude (2002)
This paper examines Keynes's genuine reasoning which is in accordance with his theory of the effective demand and his rejection of the orthodox theory which considers employment as a variable determined within a comprehensive price system. The paper suggests that the principle of effective demand is linked to a theory of income distribution where profits are a redistributed share of factor income. The payment of wages creates the money income necessary to pay for the output: measured in wage-units, income (demand) and output (supply) are identical. However, the equality of supply and demand prices is conditional, the profitability of production (and hence the employment offercd by firms) being thus subordinated to the sanction of markets.